Gaya Skandinavia Pada Ilustrasi Flora Marimekko - Citra Kemala Putri (Universitas Informatika dan Bisnis Indonesia, 2021)
The Scandinavian style is one of the styles that has big influence on the development of interior design, product and visual in the world. The Scandinavian style is influenced by several things including folk culture, as well as local and international historical events. Marimekko is a Finnish and Scandinavian-style pioneered company that was founded in 1951.By today, Marimekko has produced thousands of illustrations which are used as patterns on dresses, home furnishings, etc. The objects those Marimekko's illustrations usually used such as geometric, abstract and floral objects. This study is analizing the influence of the Scandinavian style on the floral illustrations of Marimekko’s pattern illustrations. The case of this study are several Marimekko illustrations entitled